The General Impossibility of Neoclassical Economics - Fine, Ben (Universidad Autónoma de Nuevo León, 2011)
This article recalls how neo-classical economics prides itself both on its mathematical rigour and on the universal applicability of its principles, and how, on this basis, “economics imperialism” is colonising the subject matter of the other social sciences. Critics of the mainstream have emphasised the conceptual and theoretical weaknesses of reliance upon axiomatic deductivism and methodological individualism of a special type, as well as denying the image that the mainstream has of itself as emulating the natural sciences. In a complementary critique, this article demonstrates, by drawing upon Russell’s logical paradoxes, how results from within mathematics itself, as opposed to its application, impose unnoticed limitations upon the scope and consistency of the mainstream. JEL Classification: B41.